Ochrona danych osobowych w wybranych państwach Azji - Abu Gholeh, Magdalena; Kuźnicka-Błaszkowska, Dominika (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
Personal data protection and individual’s right to privacy are one of the most important issues in recent years. In order to ensure the informational autonomy of individuals the European Parliament and the Council have introduced the Regulation 2016/679 of the European Parliament and of the Council of 27 April 2016 on the protection of natural persons with regard to the processing of personal data and on the free movement of such data, and repealing Directive 95/46/EC (General Data Protection Regulation). The basic aim of this legislation is to ensure the effective protection of personal data, as well as to harmonize and enhance the EU’s internal market. However the regulation would not be able to achieve those goals without adequate provisions applicable to processors and controllers from countries outside the Union that offer goods and services to data subjects who are in the EU. This monograph aims at examining whether the use of services provided by Asian entrepreneurs ensures the security of personal data processing. Given the cultural diversity of Asian countries and the scope of services provided by them, it is relevant to examine local data protection regimes. The holistic analysis requires evaluation of the legislation in force and it’s application. This study enabled to identify Asian countries that provide an adequate level of data protection. Thus processing operations taken by entities originating from those countries should be secure from the perspective of EU personal data protection law
Keywords: personal data protection; right to privacy; transfer of personal data to third countries; Asia; GDPR; APAC countries; MENA countries